Chromosome-level haplotype-resolved genome of the tropical loach (Oreonectes platycephalus) - Xi Wang; Dandan Wang; Hongbo Wang; David Dudgeon; Kerry Reid; Juha Merilä (Scientific Data)
Abstract The flat-headed loach (Oreonectes platycephalus) is a small fish inhabiting headwaters of hillstreams of southern China. Its local populations are characterized by low genetic diversity and exceptionally high differentiation, making it an ideal model for studying small population isolates’ persistence and adaptive potential. However, the lack of Oreonectes reference genomes limits endeavours toward these ambitions. We assembled the first haplotype-resolved chromosome-level genome of the genus Oreonectes using PacBio HiFi and Hi-C technologies. This genome consists of two haplotypes (24 pseudo-chromosomes in each), with sizes of 565.68 Mb (haplotype A) and 521.13 Mb (haplotype B) and scaffold N50 lengths of 22.80 Mb and 21.91 Mb, respectively. Chr01 was identified as the likely sex chromosome pair. After masking repetitive elements which accounted for 34.43% to 36.44% of the genome, there are 27,127 protein-coding genes in haplotype A and 25,576 in haplotype B. The availability of this haplotype-resolved chromosome-level reference genome will facilitate the study of population and conservation genetics of the flat-headed loach and other Oreonectes species.